Investigation of the magnetic ground state of GaV4S8 using powder neutron diffraction. (24th May 2021) - Holt, S J R; Ritter, C; Lees, M R; Balakrishnan, G
Abstract: The magnetic ground state of polycrystalline Néel skyrmion hosting material GaV4 S8 has been investigated using ac susceptibility and powder neutron diffraction. In the absence of an applied magnetic field GaV4 S8 undergoes a transition from a paramagnetic to a cycloidal state below 13 K and then to a ferromagnetic-like state below 6 K. With evidence from ac susceptibility and powder neutron diffraction, we have identified the commensurate magnetic structure at 1.5 K, with ordered magnetic moments of 0.23(2) μ B on the V1 sites and 0.22(1) μ B on the V2 sites. These moments have ferromagnetic-like alignment but with a 39(8)° canting of the magnetic moments on the V2 sites away from the V4 cluster. In the incommensurate magnetic phase that exists between 6 and 13 K, we provide a thorough and careful analysis of the cycloidal magnetic structure exhibited by this material using powder neutron diffraction.